Performance Efficiency of Banana Leaf Craft Supply Chain and it’s Improvement Solution: Dea-Vrs Approach - Pratiwi S, Aprilia Desi; Setiawan, Budi; Andriani, Dwi Retno (IDFoS Indonesia, 2024)
This research aimed to analyze the technical efficiency of the performance of craftsmen at UD. Barokah Tani. Respondents were selected using purposive sampling and were craftsmen at UD. Variables were selected with reference to the Supply Chain Operation Reference or SCOR 12.0. The analysis was conducted using the Data Envelopment Analysis (DEA) approach of the VRS model with input oriented. The results of the study through the DEA VRS approach the majority of craftsmen who were at a high level of efficiency with a value between 0.824 - 0.999 were 18 people (69%). Then craftsmen at a moderate level with a TE value between 0.824 - 0.999 as many as 5 people (19%). Finally, craftsmen at the full efficient efficiency level with a value of 1.00 as many as 3 craftsmen or 12%. Peer group result is a reference for other DMUs for DMUs that are not yet efficient to refer to DMUs that are already efficient. For example DMU 2, DMU 2 can refer to DMU 11 and 7 where these DMUs are DMUs that are considered relevant to DMU 2. It can be seen in the table that the efficient DMUs are DMU 1, DMU 7 and DMU 11. DMU 1 is referred to by 4 DMUs, DMU 7 is referred to by 9 DMUs and DMU 11 is referred to by 23 other DMUs. This means that the DMU that most references other efficient DMUs is DMU 11, which is 23 DMUs. Each DMU can improve efficiency by reducing the input value of its variables. A total of 20 DMUs need to reduce raw material costs, 23 DMUs need to reduce shipping costs, and 1 DMU needs to reduce labor costs. In addition, 17 DMUs need to reduce cash to cash, and 21 DMUs need to reduce lead time.